Synthesis and Characterization of Graphene-Cu Composite Via Hydrothermal Method - Omoniyi, F. O.; Alabi, A. B.; Salawu, M. A.; Buba, A. D. A. (Journal of Sustainable Materials Processing and Management, 2022)
In this paper, graphene-copper composite was synthesized via hydrothermal method using different compositions from 5 to 25%. The grain size and copper composition are observed to decrease proportionally to increase in band gap. The effect of composition fluctuate the peaks shift. The peak increased linearly with increasing temperature for each composition. The band gap reduces with increasing temperature for each composition. Short calcined duration on samples is observed to cause a little lower band gap value than that of longer duration. The thermal treatment of graphene oxide (GO) has been observed to cause changes in its quality, size and shape.